2022
DOI: 10.3390/foods11162415
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Antimicrobial Peptides: Novel Preservatives for the Food Industry

Abstract: Food spoilage is a widespread issue brought on by the undesired growth of microbes in food products. Thousands of tons of usable food or food products are wasted every day due to rotting in different parts of the world. Several food preservation techniques are employed to prevent food from rotting, including the use of natural or manufactured chemicals or substances; however, the issue persists. One strategy for halting food deterioration is the use of plant-derived antimicrobial peptides (AMPs), which have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 111 publications
0
12
0
Order By: Relevance
“…Plant-derived AMPs: Plants produce AMPs as a component of their innate defence mechanism against pathogens. Some of the significant plant-derived AMPs include defensins, 2S albumins, glycine-rich proteins, lipid transfer proteins, snakins, thionins, cyclotides, and napins [ 60 ]. For instance, a recombinant plant AMP from tomatoes, when overexpressed in E. coli , was shown to be active against a host of fungi and bacteria [ 61 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Plant-derived AMPs: Plants produce AMPs as a component of their innate defence mechanism against pathogens. Some of the significant plant-derived AMPs include defensins, 2S albumins, glycine-rich proteins, lipid transfer proteins, snakins, thionins, cyclotides, and napins [ 60 ]. For instance, a recombinant plant AMP from tomatoes, when overexpressed in E. coli , was shown to be active against a host of fungi and bacteria [ 61 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Plant-derived antimicrobial peptides, tea polyphenols, herbs and spices, and other plant-derived preservatives are widely used in the preservation of FWN (Hou et al, 2017;Li et al, 2014). Antimicrobial peptides are a class of biologically active small molecule peptides that can exert antibacterial effects on both gram-positive and gram-negative bacteria by destroying the integrity of cell membranes (Baindara & Mandal, 2022). Hou et al (2017) found that more than 2.0 mg/g of glycinin basic polypeptide (GBP) extracted from natural soybeans effectively preserved FWN for 4 days at 4 • C, which improved the sensory quality of FWN.…”
Section: Plant Extractsmentioning
confidence: 99%
“…Mohamad Asri et al found that low molecular mass peptides generated from palm kernel cake via solid state lacto-fermentation could extend the shelf life of bread, and when added to the bread at 2000 mg/kg, the peptide mixture successfully delayed fungal growth, thus extending the shelf life of bread for up to 10 days . Baindara et al also reviewed the application of antimicrobial peptides as preservatives in the food industry . Active peptides also play a variety of roles in food formulations as color preservative, acidity regulator, anticaking agent, emulsifier, and thickener.…”
Section: Application Of Plant Protein-derived Active Peptides In the ...mentioning
confidence: 99%
“…178 Baindara et al also reviewed the application of antimicrobial peptides as preservatives in the food industry. 5 Active peptides also play a variety of roles in food formulations as color preservative, acidity regulator, anticaking agent, emulsifier, and thickener. This is because they can improve the technological properties of foods, including emulsification, foaming, solubility, water holding capacity, and oil binding capacity.…”
Section: Application Of Plant Protein-derived Active Peptides In the ...mentioning
confidence: 99%
See 1 more Smart Citation